DETEKSI DINI KANKER PAYUUDARA MELALUI PEMERIKSAAN PAYUDARA SENDIRI PADA WS DI DESA BATUBULAN KANGIN GIANYAR TAHUN 2019 - Ni Ketut Somoyani (Jurnal Pengabmas Masyarakat Sehat (JPMS), 2020)
Breast cancer is a malignancy originating from the milk glands, glandular channels and supporting breast tissue. Breast cancer can be avoided if women know how to prevent the occurrence of the disease. One of them is doing breast self-examination to detect breast cancer early. The purpose of this community service is to increase knowledge and attitudes of Women of childbearing age in conducting breast self-examination in Batubulan Village, , Sukawati, Gianyar. The number of the targets participating in this activity was 55 people. The method used is lectures, questions and answers and guidance on how to realize. Before counseling, a pre-test with 22% results in the good category and 55% with a positive attitude about early detection of breast cancer through awareness, while the post-test results showed 80% good knowledge and 100% with a positive attitude. All targets choose to have regular breast checks every month even though there are no complaints. Health workers are expected to continue the health promotion program specifically in the field of reproductive health so that it is carried out routinely atthrough integrated service activities or at the time of service at the community of health